Autologous Concentrated Bone Marrow Grafting for the Treatment of Osteonecrosis of the Humeral Head: A Report of Five Shoulders in Four Cases - Takeshi Makihara; Tomokazu Yoshioka; Hisashi Sugaya; Masashi Yamazaki; Hajime Mishima (Case Reports in Orthopedics)
Five shoulders in four patients affected by advanced osteonecrosis of the humeral head were treated with autologous concentrated bone marrow grafting. Bone marrow sample was aspirated from the iliac crests, concentrated by a centrifugation technique, and injected into the necrotic site. The shoulders were evaluated radiologically with X-ray scoring and clinically with measurement of range of motion and pain score (visual analogue scale, VAS). The mean follow-up period was 49.4 (range, 24–73) months. The concentration ratio of nucleated cells was calculated and the number of transplanted mesenchymal stem cells (MSC) was estimated by a colony-forming assay. All four shoulders with stage 3 disease achieved joint sparing. One shoulder with stage 4 disease required replacement surgery. Clinical evaluation of the spared joints showed improvement in range of motion in two cases and deterioration in two cases. VAS scores were 0 after surgery in three cases. The mean concentration ratio was 2.73, and the mean number of transplanted MSC was 1125. The outcomes of autologous concentrated bone marrow grafting for advanced osteonecrosis of the humeral head were varied. Further research is needed to determine the effectiveness and the indications of the present surgery.